Extracting Benefits from Standardization of Digital Forensic Practices. (10th October 2019) - Cusack, Brian
Abstract: Standardization offers consistencies for interoperability between jurisdictions and organizational entities. In some instances, accreditation and certification services are available to assure the reputational transfer of conformance and the compliance with best practice requirements. The impact of these benefits is a more predictable environment in which to deliver sensitive and high-risk services, leading to the reduction in failures and the enhancement of inter-party trust. In this article, the case of international standardization for digital forensic and related services is articulated as an example of structured planning for robust processes and practices that have user trust. Political and economic expediency has always reduced the implementation of standardization to functional attributes and short-term returns. The advocacy is for the long-term investment in standardization and the creation of trusted practices for predictable and robust scientific procedures in the transfer of operational knowledge and the preservation of digital evidences.